A aplicação da Lei Geral de Proteção de Dados pessoais na administração pública : um estudo em uma universidade federal - MIRANDA, Igor Bega de (2025)
The increasing use of technology has sparked global discussions on the creation of legislation addressing the protection of personal data and privacy in the digital sphere. In this context, several countries have sought to regulate data protection to ensure privacy and security of personal data. Brazil’s General Data Protection Law (LGPD), inspired by the European Union’s General Data Protection Regulation (GDPR), introduced a data protection framework that applies to both the public and private sectors, promoting fundamental rights related to privacy and the free development of personality. Against this backdrop, this study aimed to investigate how the LGPD has been implemented at the Federal Rural University of Pernambuco (UFRPE), evaluating the actions taken, the challenges faced, and the institution's level of maturity regarding data protection, in order to propose measures to strengthen personal data protection at UFRPE. Methodologically, the research is characterized as applied, descriptive, and a case study, using documentary and field data. As for its approach, the study is of a mixed nature, combining qualitative and quantitative analysis. The results indicated that actions are being taken to promote personal data protection, despite existing challenges, especially those related to budgetary constraints. In this context, an intermediated level of maturity in relation to the LGPD was identified, which will require l long-term investments to consolidate a culture of personal data protection at UFRPE. It is concluded that the General Data Protection Law (LGPD) is being applied at UFRPE with consistent efforts by the institution to comply with the regulation. These initiatives demonstrate the institution’s commitment to building a culture of privacy and personal data protection.